Multimorbidity, polypharmacy and inappropriate prescribing in elderly patients with atrial fibrillation: A report from the China Atrial Fibrillation Registry Study - Guo, Xueyuan; Li, Mengmeng; Du, Xin; Jiang, Chenxi; Li, Songnan; Tang, Ribo; Sang, Caihua; Yu, Ronghui; Long, Deyong; Dong, Jianzeng; Ma, Changsheng (Frontiers in Cardiovascular Medicine, 2022)
Background Multimorbidity, polypharmacy and inappropriate prescribing is common in elderly patients worldwide. We aimed to explore the current status of multimorbidity, polypharmacy and the appropriateness of pharmacological therapy among elderly patients with atrial fibrillation (AF) in China. Materials and methods We randomly selected 500 patients aged 65 years or older from the China AF Registry study. Multimorbidity was defined as ≥2 comorbidities and polypharmacy was defined as ≥5 long-term prescribed drugs. Appropriateness of prescribing was evaluated using the Screening Tool of Older People’s Prescriptions/Screening Tool to Alert to Right Treatment (STOPP/START) criteria version 2. Patients’ attitudes toward polypharmacy were evaluated by the Patients’ Attitudes Towards Deprescribing (PATD) questionnaire. Results Among the 500 patients included (mean age 75.2 ± 6.7 years, 49.0% male), 98.0% had multimorbidity and 49.4% had polypharmacy. The prevalence of potentially inappropriate medications (PIMs) and potential prescribing omissions (PPOs) was 43.6% (n = 218) and 71.6% (n = 358), respectively. Traditional Chinese medicine attributed largely to PIMs. Anticoagulants were the most common PPOs. Many clinical factors increased the risk of PIMs and PPOs. However, polypharmacy increased the risk of PIMs (OR 2.70, 95%CI 1.78–4.11; p < 0.0001), but not PPOs. In addition, 73.7% patients with polypharmacy were willing to have one or more of their medications prescribed if advised by their doctor. Conclusion Multimorbidity and polypharmacy were highly prevalent in elderly patients with AF in China. A high prevalence of inappropriate prescribing was also observed. Therefore, much more attention should be paid to the serious health problem in the elderly population.